Penerapan Metode Dempster Shafer Untuk Deteksi Awal Gangguan Mental Pada Lansia - Milla Rosiana Dewi (2022)
Mental disorders are a decrease in a person's ability to carry out activities accompanied by feelings of restlessness, insecurity and decreased mental function. (Hamid, 2017) Mental disorders can happen to anyone, including the elderly. Mental disorders in the elderly need more attention as well as physical health. This research is a system design with the aim of building expert applications that can help make it easier for users to make early detection of mental disorders in the elderly. The dempster shafer method used in building this expert system. The dempster shafer method is a mathematical theory based on belief functions for proof and plausible reasoning and the programming languages used to design this system are PHP, HTML and CSS. The results of this study can be seen that the expert system provides information about mental disorders and helps the early recognition of mental disorders in the elderly based on the symptoms felt.